2011
DOI: 10.1111/j.1600-0404.2010.01468.x
|View full text |Cite
|
Sign up to set email alerts
|

Cerebrovascular reactivity to l-arginine in the anterior and posterior cerebral circulation in migraine patients

Abstract: OBJECTIVE - Cerebral infarction preferentially affects the posterior cerebral artery distribution in migraine patients. The results obtained from the few known studies that have compared the anterior and posterior cerebral endothelial function are contradictory. To the best of our knowledge, cerebrovascular reactivity to L-arginine (CVR), measured by transcranial Doppler sonography (TCD), has not been previously used to determine the posterior cerebral endothelial function in migraine patients with (MwA) and w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
44
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(49 citation statements)
references
References 32 publications
(65 reference statements)
3
44
2
Order By: Relevance
“…In conformity with prior studies, AIS patients with migraine more often presented symptoms from the posterior circulation and had more occipital and cerebellar infarctions (5,6,31). Our findings suggest that areas of the brain associated with migraine symptoms, for example, visual symptoms from the occipital cortex, might also be more susceptible to infarction in patients with migraine, or that cerebral ischaemia in the posterior region is especially prone to induce CSD in patients with migraine.…”
Section: Discussionsupporting
confidence: 76%
“…In conformity with prior studies, AIS patients with migraine more often presented symptoms from the posterior circulation and had more occipital and cerebellar infarctions (5,6,31). Our findings suggest that areas of the brain associated with migraine symptoms, for example, visual symptoms from the occipital cortex, might also be more susceptible to infarction in patients with migraine, or that cerebral ischaemia in the posterior region is especially prone to induce CSD in patients with migraine.…”
Section: Discussionsupporting
confidence: 76%
“…A study involving 30 patients with migraine found reduced mean BHI in the BA in patients with migraine with aura (0.83) compared to controls (1.39) and migraine without aura (1.42; p<0.001) 13. In another study, cerebral VMR to l-arginine was significantly impaired in the PCAs of patients with migraine (without aura: 14.4, with aura: 14.3) compared to controls (21.3; p=0.002) 24. These findings are quite similar to ours.…”
Section: Discussionmentioning
confidence: 90%
“…A study on silent posterior circulation infarcts in migraine proposed a combination of hypoperfusion during migraine attack and artery to artery embolism to account for these lesions 26. In migraine with aura, cortical spreading depression is thought to alter blood–brain barrier permeability and result in local ischaemia which aggravates the post ictal hypoperfusion 24. Migraineurs do not have increased predisposition to atherosclerosis, which makes artery to artery embolism less likely 27.…”
Section: Discussionmentioning
confidence: 99%
“…65 Transcranial Doppler Decreased reactivity to L-arginine in the posterior cerebral artery. 68 Voxel-based morphometry Decreased grey matter density in the frontal, parietal, and temporal lobes; 82 increased in the periaqueductal grey. 71,72 Decreased grey matter density in chronic vs episodic migraine: bilaterally in the anterior cingulate cortex, left amygdala, left parietal operculum, left middle and inferior frontal gyri, right inferior frontal gyrus, and insula.…”
Section: Modality Findingsmentioning
confidence: 99%
“…Most animal studies, however, suggest that the posterior cerebral circulation is subject to more basal vasomotor control to nitric oxide than the anterior cerebral circulation. 67 Perko and colleagues 68 used transcranial Doppler sonography to determine the posterior cerebral endothelial function in migraine patients. Mean arterial velocity in the MCA and the posterior cerebral artery (PCA) of migraineurs was measured before and after infusion of L-arginine (precursor to nitric oxide, a potent vasodilator), and cerebrovascular reactivity to L-arginine was then calculated.…”
Section: 91111mentioning
confidence: 99%